The Influence of Competence and Communication on Employee Performance of Internal Audit Work Unit At PT Bank Mandiri (Persero), Tbk With Mediation Variable Job Satisfaction - Marwah Aya Shofia (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2020)
This study aims to analyze the influence of competence and communication on internal audit employees' performance at PT Bank Mandiri (Persero) Tbk with the mediating variable of Job Satisfaction. The population in this study were 284 employees of the internal audit of PT Bank Mandiri Tbk. Whereas in this study using saturated samples, the entire population of this study became research respondents. The data collection method is by distributing questionnaires as a primary data collection tool. Furthermore, the data is processed and analyzed using the Amoss 26 Structural Equation Models method. This study uses competency and communication independent variables as well as employee performance-dependent variables and job satisfaction mediation variables. The results of the study prove that there is an effect of competence on job satisfaction; there is an effect of communication on job satisfaction; there is an influence of competence on performance; there is an effect of communication on performance; there is an effect of job satisfaction on performance; there is an influence of competence on performance through job satisfaction; there is an effect of communication on performance through job satisfaction.